2023
DOI: 10.1038/s41467-023-38047-x
|View full text |Cite
|
Sign up to set email alerts
|

Computational design and molecular dynamics simulations suggest the mode of substrate binding in ceramide synthases

Abstract: Until now, membrane-protein stabilization has relied on iterations of mutations and screening. We now validate a one-step algorithm, mPROSS, for stabilizing membrane proteins directly from an AlphaFold2 model structure. Applied to the lipid-generating enzyme, ceramide synthase, 37 designed mutations lead to a more stable form of human CerS2. Together with molecular dynamics simulations, we propose a pathway by which substrates might be delivered to the ceramide synthases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…In this model, the substrates bind orthogonally, and the long-chain base would access the active site through a side entrance located near the membrane mid-point, where it would bind parallel to the membrane plane. This proposed substrate-binding arrangement is similar to that of small-molecule membrane-bound Oacyltransferases (MBOATs) and led to the suggestion that CerS may catalyze the direct transfer of the acyl chain from acyl-CoA to the long-chain base in a single step involving the two active site histidines 50 . In addition, while this manuscript was under review, the cryo-EM structure of yeast Lac1p bound to an acyl-CoA was reported.…”
Section: Discussionmentioning
confidence: 88%
See 2 more Smart Citations
“…In this model, the substrates bind orthogonally, and the long-chain base would access the active site through a side entrance located near the membrane mid-point, where it would bind parallel to the membrane plane. This proposed substrate-binding arrangement is similar to that of small-molecule membrane-bound Oacyltransferases (MBOATs) and led to the suggestion that CerS may catalyze the direct transfer of the acyl chain from acyl-CoA to the long-chain base in a single step involving the two active site histidines 50 . In addition, while this manuscript was under review, the cryo-EM structure of yeast Lac1p bound to an acyl-CoA was reported.…”
Section: Discussionmentioning
confidence: 88%
“…This hydrocarbon chain lies against the conserved Trp318 of TM7 just beneath the active site. Mutation of the corresponding residue in CerS5 to an alanine has been previously shown to abolish enzymatic activity 50 . In contrast, introducing a phenylalanine at this position by a W318F mutation in CerS6 retained approximately wild-type levels of activity (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Further experimental analysis will be required to decide between these possibilities. In a companion paper, we demonstrate that mPROSS can also increase the stability and expression levels while retaining almost wild‐type activity levels in a human membrane enzyme based on its AlphaFold2 model structure (Zelnik et al, 2023 ). In that case, two homologous human ceramide synthases were subjected to modeling and design, and for one of these, a large increase in expression was observed while a few designs exhibited some decrease in activity at the highest mutation levels.…”
Section: Discussionmentioning
confidence: 99%